Tracking Down Cult: Production, Function and Content of Chalices in Iron Age Philistia. (May 2014) - Gadot, Yuval; Finkelstein, Israel; Iserlis, Mark; Maeir, Aren M.; Nahshoni, Pirhiya; Namdar, Dvory
<x content-type="archive" xml:space="preserve">Abstract</x> The paper attempts to integrate the study of the manufacture, function and discard of chalices from three sites in Philistia in order to form a coherent 'life-cycle story' of this vessel type. The analyses include examination of the sources of the ceramic raw material using petrography; study of the modes of manufacture, employing visual inspection and ethnographic data; and examination of the function of these vessels, using organic residue analysis. By combining these analytic perspectives, the authors shed new light on cultic practices in Iron Age Philistia and offer an alternative view of Philistine identity.